Analisis Kualitas Website Alumni Stikom Bali Menggunakan Metode Webqual - Santiari, Putu Linda; Rahayuda, I Gede Surya (Jurnal Teknologi Informasi dan Ilmu Komputer, 2018)
STIKOM Bali Alumni Website at http://alumni.stikom-bali.ac.id domain is online information media which is used to give information to alumni STIKOM Bali. So far there have been complaints about the documentation, information on alumni websites that have not been updated. Therefore, quality evaluation is needed to know the problems that exist in the system and in order to achieve certain goals effectively, efficiently, and achieve user satisfaction. Based on these problems, then the research was published under the title Analysis Quality Alumni STIKOM Bali Website Using Webqual. In this research using Webqual method to measure quality of information and quality of interaction. Research begins with data collection, website testing, and analysis. Results from the output data to find out the quality problems that exist and become a reference for further improvement. In evaluating the quality of information and quality interaaksi there are problems of quality problems. From the problems found then made a quizioner to know the quality of information and the quality of interaction based on the problems found. Before this quizioner is distributed then the validity and reliability test will be done using SPSS software. If the quizioner is valid and reliable then the quizioner will be distributed and then evaluated. From the dissemination of questionnaires to several students, there are 3 indicators that are rejected, so it needs to be improved. The three indicators that need to be improved namely the information provided is difficult to understand, good reputation, and sense of community.